Multilevel predictors of controlled CD4 count and blood pressure in an integrated chronic disease management model in rural South Africa: a panel study - Stephen Tollman; Kathleen Kahn; Kerstin Klipstein-Grobusch; Soter Ameh; Francesc X Gómez-Olivé (BMJ Open)
Objective In 2011, The National Department of Health introduced the Integrated Chronic Disease Management (ICDM) model as a pilot programme in selected primary healthcare facilities in South Africa. The objective of this study was to determine individual-level and facility-level predictors of controlled CD4 count and blood pressure (BP) in patients receiving treatment for HIV and hypertension, respectively.Design A panel study.Setting and participants This study was conducted in the Bushbuckridge Municipality, South Africa from 2011 to 2013. Facility records of patients aged ≥18 years were retrieved from the integrated chronic disease management (ICDM) pilot (n=435) and comparison facilities (n=443) using a three-step probability sampling process. CD4 count and BP control are defined as CD4 count >350 cells/mm3 and BP <140/90 mm Hg. A multilevel Least Absolute Shrinkage and Selection Operator binary logistic regression analysis was done at a 5% significance level using STATA V.16.Primary outcome measures CD4 (cells/mm3) count and BP (mm Hg).Results Compared with the comparison facilities, patients receiving treatment in the pilot facilities had increased odds of controlling their CD4 count (OR=5.84, 95% CI 3.21–8.22) and BP (OR=1.22, 95% CI 1.04–2.14). Patients aged 50–59 (OR=6.12, 95% CI 2.14–7.21) and ≥60 (OR=7.59, 95% CI 4.75–11.82) years had increased odds of controlling their CD4 counts compared with those aged 18–29 years. Likewise, patients aged 40–49 (OR=5.73, 95% CI 1.98–8.43), 50–59 (OR=7.28, 95% CI 4.33–9.27) and ≥60 (OR=9.31, 95% CI 5.12–13.68) years had increased odds of controlling their BP. In contrast, men had decreased odds of controlling their CD4 count (OR=0.12, 95% CI 0.10–0.46) and BP (OR=0.21, 95% CI 0.19–0.47) than women.Conclusion The ICDM model had a small but significant effect on BP control, hence, the need to more effectively leverage the HIV programme for optimal BP control in the setting.